ANALISIS GAYA BELAJAR SISWA KELAS V TERHADAP HASIL BELAJAR PADA PEMBELAJARAN IPAS DI SD NEGERI PANDEAN LAMPER 02 SEMARANG - Iin Injzah Murtina; Eka Sari Setianingsih; Qoriati Mushafanah (STKIP Subang, 2025)
This research is motivated by the fact that each student has a different learning style so that it has an impact on their learning outcomes. In learning Natural and Social Sciences (IPAS) at SD Negeri Pandean Lamper 02 Semarang, teachers have used various learning methods and models, but their application has not been consistent. This causes differences in learning outcomes, where some students are able to achieve KKM, while others are still below the minimum completeness criteria. This condition encourages researchers to analyze more deeply the relationship between learning style and student learning outcomes. The formulation of the problem in this study is: 1) What is the tendency of the learning style of grade V students in learning science at SD Negeri Pandean Lamper 02 Semarang?. 2) How is the analysis of the learning style of grade V students on the learning outcomes of science learning at SD Negeri Pandean Lamper 02 Semarang?. The objectives to be achieved in this study are: 1) To describe the tendency of learning styles of grade V students in social studies learning at SD Negeri Pandean Lamper 02 Semarang. 2) To describe the results of the analysis of the learning style of grade V students on the learning outcomes of science learning at SD Negeri Pandean Lamper 02 Semarang. This type of research uses a qualitative approach with a descriptive method. Data were obtained through observation, interviews, questionnaires, and documentation of learning outcomes in the form of daily test scores in science learning. The subject of this study is grade V students of SD Negeri Pandean Lamper 02 Semarang which totals 19 students consisting of 6 female students and 13 male students. The results of the study showed that the learning style of grade V students at SD Negeri Pandean Lamper 02 Semarang was visual learning style, with a percentage of 52.63% (10 students). Students with visual learning styles also obtained the highest average score of 81, compared to auditory with an average of 71.6 and kinesthetic with an average of 63.3. Based on this study, the advice conveyed to teachers is that teachers are more varied in applying learning methods by paying attention to all learning styles of each student, especially for kinesthetic students who need direct practice In addition, students are expected to be able to recognize their respective learning styles to improve learning outcomes